JOB EMBEDDEDNESS AMONG PRIVATE COLLEGE TEACHERS: A COMPREHENSIVE INVESTIGATION (Contemporary Journal of Social Science Review, 2024)
This study examines the job embeddedness of private college teachers, focusing on the dimensions of community fit, organizational fit, and organizational and community sacrifice. Using a descriptive survey methodology, the study gathered teachers’ perceptions on these factors, analyzing mean scores and standard deviations to assess overall embeddedness levels. Findings indicate a moderate level of job embeddedness across all dimensions. "Community Fit" scored the highest among sub-dimensions, suggesting that teachers feel somewhat integrated within their local communities. Within organizational fit, the compatibility of organizational and personal values contributed most to a sense of embeddedness, while lower embeddedness levels were noted in perceptions of group cohesion and utilization of skills. The "Organization Sacrifice" factor showed that teachers were most concerned with the sacrifices involved in leaving their positions, including loss of compensation and promotional opportunities, though engagement in other areas like healthcare benefits and respect at work scored lower. Demographic analysis revealed no significant differences in job embeddedness based on gender, age, or marital status, though experience and academic qualifications did show some influence. These findings offer insights into private college teachers' levels of attachment and the aspects of job embeddedness that could impact turnover intentions, suggesting areas for improvement in organizational policies to enhance teacher retention and engagement.